2015
DOI: 10.1007/s11060-015-1819-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant near TERC influencing the risk of gliomas with older age at diagnosis in a Chinese population

Abstract: A recent genome-wide association study has identified an association between rs1920116 near TERC and high-grade glioma in populations of European ancestry. In order to evaluate the effect of the SNP rs1920116 near TERC in the Chinese population, we examined associations of this candidate SNP with glioma in a sample of 1970 Chinese Han individuals. SNP genotype data were available for 980 Chinese glioma patients and 990 healthy controls. Logistic regression analyses were performed to evaluate the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Somatic mutations in the promoter of TERT are found in a large proportion of adult gliomas [ 26 , 27 ], where they lead to aberrant binding of the GABP transcription factor and telomerase reactivation [ 28 ]. Our single-locus analyses show an association between inherited variation in the telomerase component genes TERC and TERT and glioma risk, as previously reported [ 1 - 3 , 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…Somatic mutations in the promoter of TERT are found in a large proportion of adult gliomas [ 26 , 27 ], where they lead to aberrant binding of the GABP transcription factor and telomerase reactivation [ 28 ]. Our single-locus analyses show an association between inherited variation in the telomerase component genes TERC and TERT and glioma risk, as previously reported [ 1 - 3 , 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…They reported significant associations at 5p15.33 [rs2736100, P = 3.69 × 10 −4 , OR = 1.26 (1.11–1.43), 11q23.3 (rs498872, P = 3.80 × 10 −6 , OR = 1.38 (1.20–1.57) and 20q13.3 (rs6010620, P = 2.79 × 10 −6 , OR = 1.39 (1.20–1.59)], but not at 8q24.21 or 9p21.3. An additional study of 980 cases and 990 controls reported an association between rs1920116 at 3q26.2 and glioma in the Chinese population (123). Aside from these studies there is a paucity of data currently available for glioma genetic risk in non-European populations.…”
Section: Perspectives From Glioma Gwasmentioning
confidence: 99%
“…However, environmental and occupational exposures have been identi ed to be associated with the occurrence and development of glioma, especially high-dosage ionizing radiation [3]. In addition, genetic factors are also given a pivotal contribution to the occurrence and prognosis of glioma [4][5][6]. Several association studies have revealed that single nucleotide polymorphisms (SNPs) were associated with glioma risk and survival [7][8][9].…”
Section: Introductionmentioning
confidence: 99%